POLISH SOCIETIES ROLE IN THE “THIRD SECTOR” DEVELOPMENT IN VOLYN - Stronskyy, Henrikh; Panyshko, Halyna (The Modern Higher Education Review, 2019)
The article analyzes the activities of Polish societies with the status of civic organizations in their professional, cultural and educational activities. Public associations (associations, unions) operating in the Volyn region provide an opportunity to determine the level of development of the “third sector” in the region. Each society has its own structure and governing bodies, in its activity the statute of the partnership is used, carrying out its activities in accordance with the Constitution of Ukraine, the Law of Ukraine “On Public Associations”. Societies do not carry out commercial and political activities. The article highlights several Polish societies that operate in Volyn, among them: the Society of Polish Culture in Volyn named after Eva Felinskaya. Society of Polish Culture named after T. Kosciuszko. Society of Polish Culture of Gorohovshchyna named after Y. Slovatsky, Volyn Society of Polish Doctors, Volyn Branch of the Association of Polish Teachers, Society of Polish Artists "Barwy Kresowe", Polish Society of Polish Culture named after Michal Oginsky in Novovolynsk and the Society of Polish Teachers named after G. Zapolskaya. All these societies engage in scientific, educational and cultural activities aimed at the revival and development of the Polish language, literature and culture.It is concluded that the main goal of one or another organization is the national-cultural revival of the polonium, the popularization of the Polish language, and the satisfaction of the common interests of persons of Polish origin living in the Volyn region. Particularly important is the role of societies in establishing close personal contacts between Polish and Ukrainian communities. After all, the Polish minority in independent Ukraine, on the one hand, gradually revives its ethical and national traits, in particular, the native language of communication, visits to the church, develops popular culture and mentality, and on the other hand, it is increasingly integrated into Ukrainian society, joins the public-political life of the state, acts as an effective factor in the Ukrainian-Polish partnership.